The ichthyoplankton of the Cacheu river’s estuary - Santos, João Pedro Valeriano (2023)
Fish larvae are particularly sensitive to a number of factors and, since larval survival may directly influence future abundances of adult stocks, understanding how larval survival and populational fluctuations affects the yearly recruitment strength and spatial distribution of populations becomes of key importance. The main objectives of this research were to perform a taxonomic characterization of the ichthyoplankton collected along the Cacheu river, assess its biodiversity and how it fluctuates with environmental variability. To achieve this, we performed a taxonomical identification and quantification of fish larvae, down to the lowest possible taxonomic level, collected from zooplankton sampling tows at four stations along the Cacheu river, in the Republic of Guinea-Bissau (RGB). With the abundance data gathered from this, we assessed the biodiversity within the estuary and how environmental factors (i.e.: depth, O2 saturation, salinity, and temperature) drove each taxon’s distribution along the stream. Our results have shown that there seems to be no correlation between the variation of larval abundance and that of the environmental factors. However, the overall abundance was observed to decrease with depth, increase from upstream to downstream and to have different distributions in each season. We found 10 taxa in our samples: Atherinidae (no previous records of presence in the area), Carangidae, Clupeidae, Congridae, Gobiidae, Mugilidae, Syngnathidae, Clupeiformes, Heterosomata (Pleuronectiformes), and Elops. Overall, Gobiidae larvae represented the majority of the fish larvae identified, followed by Clupeidae and Carangidae. The relative difference in abundances between Clupeidae and Carangidae is in accordance with two previous studies undertaken off the coast of the RGB, however the predominance of Gobiidae is not, which may be due to the sampling environment of the present study being estuarine whereas in both previous studies it was marine. This appears to be the first study regarding taxonomic characterization of ichthyoplankton (more specifically, fish larvae) within an estuarine environment, in the RGB, and may thusly be of significance in aiding the characterization of the biodiversity of the Cacheu river, providing a baseline reference for future taxonomic studies within it.